Molecular electric dipole moments using the GVVPT2 variant of multireference perturbation theory - Theis, Daniel; Khait, Yuriy G.; Pal, Sourav; Hoffmann, Mark R. (Chemical Physics Letters, 2010)
A Lagrangian approach for electric dipoles within second order Generalized Van Vleck Perturbation Theory (GVVPT2) is presented. The Lagrangian approach for this response property requires that only one, perturbation-independent, set of simultaneous equations needs to be solved. The presented formulation is demonstrated numerically on several well studied molecules at their equilibrium bond lengths and on the complete potential energy curves of the ground and first excited states of LiH. Numerical corroboration of the expected continuity for molecular properties for the GVVPT2 method is observed. It is seen that the GVVPT2 electric dipoles are in good agreement with experiment and with other high accuracy theoretical methods. (C) 2010 Elsevier B.V. All rights reserved.